Brain MRI Radiomics Analysis of School-Aged Children with Tetralogy of Fallot. (29th October 2021) - Pu, Yiwei; Li, Songmei; Ma, Siyu; Hu, Yuanli; Hu, Qinghui; Liu, Yuting; Wu, Mengting; An, Jia; Yang, Ming; Mo, Xuming
Abstract : Introduction . Radiomics could be potential imaging biomarkers by capturing and analyzing the features. Children and adolescents with CHD have worse neurodevelopmental and functional outcomes compared with their peers. Early diagnosis and intervention are the necessity to improve neurological outcomes in CHD patients. Methods . School-aged TOF patients and their healthy peers were recruited for MRI and neurodevelopmental assessment. LASSO regression was used for dimension reduction. ROC curve graph showed the performance of the model. Results . Six related features were finally selected for modeling. The final model AUC was 0.750. The radiomics features can be potential significant predictors for neurodevelopmental diagnoses. Conclusion . The radiomics on the conventional MRI can help predict the neurodevelopment of school-aged children and provide parents with rehabilitation advice as early as possible.